Milestones in the Technology of Modified Starch in Pharmaceutical Formulation - Agnihotri, Jaya Anil (Natural Products Journal, The, 2025)
Carbohydrates, the most prevalent class of organic substances in living systems, play a variety of important roles, such as in the creation of energy, the construction of biological structures, and the synthesis of paper and food. More advanced uses of modified starch have been introduced over the past millennium, demonstrating that modified starches are promising excipients in drug delivery, an area in which their role and range of utility continuously increase. Technological advancements in the pharmaceutical field have led to the development of new and highly stable molecules with enhanced properties for novel drug delivery systems. Innovative starches from various sources present exclusive support in the development of novel dosage forms.
Keywords: technological